Knowledge and innovation in Mexican agricultural organizations - Sergio Ochoa Jiménez; Gimena Vianey Cervantes Hurtado; Carlos Armando Jacobo Hernández; José Guadalupe Flores López (Economies, 2020)
Knowledge is a determining factor in the creation of competitive advantage by generating new ways of working, which has been widely studied. However, in the agricultural sector, the contributions are minimal. Given the importance of the topic and the sector, the objective of this study is to determine the relationship between knowledge management and innovation in rural agricultural organizations in the state of Sonora in northern Mexico. A quantitative, correlational study was carried out, in which a questionnaire of 36 items with answers on a Likert scale was applied to 91 companies. The information was processed and analyzed in the SPSS program using correlation and linear regression. The results showed a positive and significant relationship between the variables under study, which supports that knowledge management in these companies, has as a consequence, innovations in them; however, it was not possible to determine the impact in economic terms. This can be taken up again in subsequent studies and in a practical sense in the companies by promoting knowledge management actions that encourage new processes, services and/or products that allow a monetary impact on them.
Keywords: M10; M19; O13; 330; organizations; primary sector; processes; products; services